2019
DOI: 10.7717/peerj.6187
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light intensity, fertilizing and season on the cirsiliol content, a chemical marker ofLeonotis nepetifolia(Lamiaceae)

Abstract: BackgroundLeonotis nepetifolia (Family Lamiaceae) is a medicinal plant from which the flavonoid cirsiliol with sedative, hypnotic, anti-inflammatory and cytotoxic activity has been extracted.MethodsSeedlings were cultivated under different levels of shade in native or fertilized modes. The content of cirsiliol was measured monthly by high-performance liquid chromatography and the total phenolic content by the Folin-Ciocalteu method. Monitoring of growth was carried out with the weekly measurement of height unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Th literature reports that Leonotis nepetifolia extracts contain the anti-inflammatory flavonoid cirsiliol (3′,4′,5-trihydroxy-6,7-dimethoxyflavone) [ 31 , 32 , 33 ], in turn, our earlier study reported high content of (+)-catechin, p-coumaric acid, m-coumaric acid and rosmarinic acid in the transformed root extract of Leonotis nepetifolia , which also may have an anti-inflammatory effect [ 17 ]. This may explain our results, since the TR extracts more effectively inhibited both IL-1β and IL-6 expression—probably due to higher concentrations of anti-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Th literature reports that Leonotis nepetifolia extracts contain the anti-inflammatory flavonoid cirsiliol (3′,4′,5-trihydroxy-6,7-dimethoxyflavone) [ 31 , 32 , 33 ], in turn, our earlier study reported high content of (+)-catechin, p-coumaric acid, m-coumaric acid and rosmarinic acid in the transformed root extract of Leonotis nepetifolia , which also may have an anti-inflammatory effect [ 17 ]. This may explain our results, since the TR extracts more effectively inhibited both IL-1β and IL-6 expression—probably due to higher concentrations of anti-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…[21], the aerial parts of the plant Isodon rubescens (also known as Rabdosia rubescens (Hemsl.) [22], and Leonotis nepetifolia (Lamiaceae) [23]. On the other hand, extracts of these plants are used in herbal medicine for inflammatory disease treatment due to their free-radical scavenging action [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…[15,16]. Cirsiliol, a flavonoid found in many plants such as Artemisia, Salvia, and Leonotis nepetifolia, has anti-inflammatory, antioxidant, antibacterial, sedative, and hypnotic effects [17][18][19][20]. It has recently been shown to exert cancer inhibition effects against non-small cell lung cancer and other cancers [21,22].…”
Section: Introductionmentioning
confidence: 99%